2021
DOI: 10.5114/aoms/111947
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in RL95-2 human endometrial cancer cells by combination treatment with docosahexaenoic acid and triacsin C

Abstract: IntroductionDocosahexaenoic acid (DHA) supplementation has been reported to negatively correlate with cancer cell proliferation and tumour development in many cancer types. Although cumulative evidence has demonstrated the apoptotic effect and cytotoxicity of DHA against tumour development in many cell types, the precise cellular and biochemical mechanisms of DHA-induced apoptosis in human endometrial cancer cells have not been investigated.Material and methodsMTT assay was performed to confirm the degree of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Consistent with the hypothesis that ACSLs support MM cell proliferation and survival, we showed that pharmacological inhibition of the ACSL family with triacsin C in human MM cell lines decreased MM cell viability and proliferation and induced apoptosis starting after 48 h of treatment. These results are consistent with reports of TriC treatment decreasing viability in human breast cancer (33), Burkitt's lymphoma (34), and endometrial (35) cell lines, and initiating apoptosis in human TP53-mutant lung, colon, and brain cancer cell lines (36). Interestingly, while most of the MM cell lines tested were TP53 mutants, MM.1S (TP53 WT ) cells were sensitive to TriC treatment, suggesting that either TriC toxicity in MM cells is independent of TP53 status, or that toxicity occurs via multiple mechanisms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the hypothesis that ACSLs support MM cell proliferation and survival, we showed that pharmacological inhibition of the ACSL family with triacsin C in human MM cell lines decreased MM cell viability and proliferation and induced apoptosis starting after 48 h of treatment. These results are consistent with reports of TriC treatment decreasing viability in human breast cancer (33), Burkitt's lymphoma (34), and endometrial (35) cell lines, and initiating apoptosis in human TP53-mutant lung, colon, and brain cancer cell lines (36). Interestingly, while most of the MM cell lines tested were TP53 mutants, MM.1S (TP53 WT ) cells were sensitive to TriC treatment, suggesting that either TriC toxicity in MM cells is independent of TP53 status, or that toxicity occurs via multiple mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…TriC has been shown to effectively inhibit the growth of human breast cancer cells (19), while in acute myeloid leukemia (AML), TriC treatment inhibits cellular viability and synergizes with other anti-AML therapies (20). In endometrial cancer, TriC decreases survival, an effect that is enhanced by the addition of omega-3 FA docosahexaenoic acid (DHA) (21). TriC also induces apoptosis in glioma cells and synergizes with the apoptosis inducer etoposide, causing substantial cytotoxicity in glioma cells both in vitro and in vivo (19).…”
Section: Introductionmentioning
confidence: 99%